On the structure of two-person, finite, zero-sum games - Wyderka, Zdzisław (Annales Mathematicae Silesianae, 1990)
The algebraical and topological structure of the set ???? (resp. ????1) of all n×m matrix games with saddle points (resp. with unique saddle point) in the space Rn×m of all such games is studied. It has been shown that ???? is a closed cone with vertex zero and includes the origin. Moreover, it is neither convex nor dense subset of Rn×m. The set ????1 is a non-convex cone which does not include the origin. It is neither closed nor open. The concept of “reserve of non-saddlexity” has been also introduced.